Key actors’ perspectives on cost-effectiveness analysis in Uganda: a cross-sectional survey - Musuuza, Jackson S.; Singer, Mendel E.; Mandalakas, Anna M.; Katamba, Achilles (BMC Health Services Research, 2014)
Cost effectiveness analysis (CEA) is a useful tool for allocation of constrained resources, yet CEA methodologies are rarely taught or implemented in developing nations. We aimed to assess exposure to, and interest in CEA, and identify barriers to implementation in Uganda. Methods: A cross-sectional survey was carried out in Uganda using a newly developed self-administered questionnaire (via online and paper based approaches), targeting the main health care actors as identified by a previous study. Results: Overall, there was a 68% response rate, with a 92% (69/75) response rate among the paper-based respondents compared to a 40% (26/65) rate with the online respondents. Seventy eight percent (74/95) of the respondents had no exposure to CEA. None of those with a master of medicine degree had any CEA exposure, and 80% of technical officers, who are directly involved in policy formulation, had no CEA exposure. Barriers to CEA identified by more than 50% of the participants were: lack of information technology (IT) infrastructure (hardware and software); lack of local experts in the field of CEA; lack of or limited local data; limited CEA training in schools; equity or ethical issues; and lack of training grants incorporating CEA. 93% reported a lot of interest in learning to conduct CEA, and over 95% felt CEA was important for clinical decision making and policy formulation. Conclusions: Among health care actors in Uganda, there is very limited exposure to, but substantial interest in conducting CEA and including it in clinical decision making and health care policy formation. Capacity to undertake CEA needs to be built through incorporation into medical training and use of regional approaches.
Keywords: Cost-effectiveness analysis; Healthcare in Uganda; Constrained resources